TFP growth in Turkey revisited: The effect of informal sector - Orhan Erem Atesagaoglu; Ceyhun Elgin; Oguz Oztunali (Central Bank Review (CBR), 2017)
In this paper, we aim to contribute to the growth literature by presenting evidence that the presence of an informal sector might significantly affect both the level as well as the course of the total factor productivity (TFP). To this end, we develop a framework where we can compare the TFP in Turkey generated by a one-sector benchmark model to the one originating from an extended model with the presence of formal and informal labor. Our results indicate that, over the course of 1950–2014, the TFP generated by the benchmark model generally underestimates the productivity of the formal sector and this underestimation is mainly observed and is widened after 1980. Moreover, we also find that the substitution between formal and informal labor significantly affects this underestimation.
Keywords: 330; TFP growth; Informal sector; CES production functions